An Exploratory Qualitative Study of Beverage Sweetening Practices in Middle Eastern Families - Abir Abdel Rahman PhD; Nada O. F. Kassem PhD; Marc Edwards PhD; Juliana Abboud PhD; Bahia Abdallah PhD, MPH, RN (Inquiry: The Journal of Health Care Organization, Provision, and Financing)
Over the last 30 years, there has been a continuing global shift in eating patterns and associated behaviors toward the consumption of foods and beverages rich in refined sugars in developed and undeveloped countries. The behavior of adding sugar to milk and other beverages has been observed as a major underlying factor in developing countries, including the Eastern Mediterranean Region. This qualitative study fills a knowledge gap by exploring the “adding sugar behavior” in primary caregivers and the underlying factors behind this common practice. In this study, a total of 26 in-depth interviews were conducted with the mothers, fathers and grandmothers of students from 4 public schools in Lebanon and thematically analyzed. The adding sugar behavior was common among the participants. Primary caregivers reported adding sugar to milk and to other beverages. Only a few primary caregivers stated that sugar was harmful and should be avoided. A common theme that emerged was that adding sugar to milk and beverages was a habit and a social norm within a locality. Findings of this innovative study in a Middle Eastern setting showed that the adding sugar behavior was influenced by specific personal and cultural behavioral factors. Strategies in future health behavior modification programs should include the children’s family and the behaviors and habits within the culture.